Sedimentology, dynamics and debris flow potential of Champadevi River, southwest Kathmandu, Nepal - Tamrakar, Naresh Kazi; Prajapati, Achut; Manandhar, Suman (Bulletin of the Department of Geology, 2008)
Mountainous and hilly regions are potential for debris flows, one of the major forms of natural disasters, which cause serious damage in downstream areas. The southwestern region of the Kathmandu Valley experienced catastrophic flows in the Champadevi River and its two tributaries (the Aitabare and the Raute Rivers) in July 2002. These rivers were investigated for morphologic, hydraulic and sedimentary characteristics to evaluate potential of debris flow in the area. The Raute and the Aitabare Rivers have tendency of headward erosion due to abrupt drop of gradient down the scarp of the alluvial fan deposit composed of unconsolidated matrix-supported gravel and mud. Because of this tendency, the rivers erode their substrate and banks, and contribute slope movements by sheding a huge amount of clasts and matrix. Therefore, instability condition of rivers and unconsolidated material available in the river courses potentially contribute for debris flow. The tractive shear stresses in the Aitabare, the Raute and the Champadevi Rivers (1.27, 1.60 and 0.48 KPa, respectively) exceeds twice the critical shear stresses required to transport 90th-percentile fraction of the riverbed material (0.14, 0.18 and 0.11 KPa). The stream powers (10.8, 17.2 and 5.1 m-kN/s/m2) of these rivers also greatly exceed the critical stream powers (0.21, 0.35 and 0.18 m-kN/s/m2) required to initiate traction transport. Because the tractive shear stresses and the stream powers that are achieved during bankfull flow are several times larger than the corresponding critical values, even the flow having stream power exceeding the critical stream power may potentially generate debris flow. doi: 10.3126/bdg.v10i0.1416 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 9-20